ANALISIS KEBIJAKAN PEMERINTAH TENTANG MANAJEMEN PENERIMAAN PESERTA DIDIK BARU ATAU PPDB - Mawardi; Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The Zoning-based New Student Admissions (PPDB) Policy is one of the government's efforts to encourage increased access to quality, equitable, and just education services. This study aims to analyze the government's policy on zoning-based PPDB. The results of the study indicate that the zoning-based PPDB policy can help improve the equality of education quality, reduce education gaps, and increase access to quality education services.